Freedom by the Book: Novels and the Future of Liberal Democracy. (20th February 2023) - Fraser, Gordon
Abstract: The scholars included in this special issue of ALH reveal not an ideology but a method—a method that depends upon the novel. Many of the scholars here suggest that by reading novels—and, in particular, by reading them well—we might extend the horizon of democratic possibility. The present essay agrees. Indeed, it suggests that novels extend the horizon of democratic possibility in three important ways: by enabling readers to think deeply about the relationship between incommensurate goods; by accounting for the role of emotion in shaping values; and by enabling readers to process and react to the inevitability of change. Ultimately, this essay suggests that novels have a role to play in fostering democratic values.As free people, we make choices about the individual and collective direction of our lives. And, in deciding, we need the examples and stories of others. We need, in other words, stories about lives lived meaningfully or unmeaningfully, with dignity or without it.